Pasture recovery with the application of agricultural gypsum associated with nitrogen fertilization (Research, Society and Development, 2020)
The presence of toxic aluminum in the soil and N deficiency are one of the main causes of degradation of cultivated pastures, mainly of the Urochloa genus. The use of agricultural gypsum for restoring soil fertility is one of the ways to recover the productive capacity of degraded areas. Given the above, the work aims to assess pasture recovery with the application of agricultural gypsum associated with nitrogen fertilization. The experimental design was randomized blocks in a 3x4 factorial arrangement, that is, absence of nitrogen, 50 kg ha-1 in the form of ammonium nitrate and 50 kg ha-1 urea, interacting with four doses of agricultural gypsum, namely: 0 ; 750; 1500 and 3000 kg ha-1 and with four replications, totaling 48 plots. The use of urea as a source of N resulted in a higher plant height (PH) when compared to the use of ammonium nitrate, representing a relative increase of approximately 12% in relation to the control. Dose of 1730.8 kg ha-1 of agricultural gypsum resulted in a maximum production of 4.97 t ha-1 of dry pasture. The linear interaction of the use of ammonium nitrate with gypsum doses shows an extremely interesting synergistic potential with this source. For dry mass of culms (CDM), the use of urea had a PMTE of 1730.8 kg ha-1 of agricultural gypsum resulting in 2.38 t ha-1. The culms dry mass of (CDM) represented 47.9% of the total dry mass of the pasture.